A Stable Heterocyclic Amino(phosphanylidene‐σ4‐phosphorane) Germylene. Issue 15 (8th March 2016) - Del Rio, Natalia; Baceiredo, Antoine; Saffon‐Merceron, Nathalie; Hashizume, Daisuke; Lutters, Dennis; Müller, Thomas; Kato, Tsuyoshi
Abstract: A new stable heterocyclic germylene, in which the divalent germanium atom lies between a nitrogen atom and a phosphanylidene phosphorane group, was synthesized. Experimental and theoretical studies revealed the peculiar effect of phosphanylidene phosphorane substituent, which is a stronger π‐donor towards germanium than an amino group is. Because of the weak phosphorus–germanium π‐bond, this new germylene compound shows an enhanced reactivity compared to classical N‐heterocyclic germylenes. Abstract : 'Germs' of a different type : A stable heterocyclic germylene, in which the divalent germanium atom lies between a nitrogen atom and a phosphanylidene phosphorane group, was synthesized. Experimental and theoretical studies revealed the peculiar effect of the phosphanylidene phosphorane substituent, which presents π‐donor abilities stronger than that of amino groups.